The potential of plant microbiota in reducing postharvest food loss. Issue 6 (26th March 2018) - Buchholz, Franziska; Kostić, Tanja; Sessitsch, Angela; Mitter, Birgit
Summary: The role of the plant microbiota in plant establishment, growth and health is well studied, but the dynamics of postharvest crop microbiota and its role in postharvest crop quality are largely unexplored, although food loss is an enormous issue worldwide. The microbiota might be especially important during crop storage by either preventing or favouring rots, or quality loss due to, for example, sprouting, saccharification, water loss or spoilage. We need more research on plant–microbe interactions in postharvest crops to be in future able to provide microbial solutions for plant production along the whole food chain from field to fork.